2012
DOI: 10.1080/17550874.2012.701670
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for local adaptation to soils or microclimate in the post-fire recruitment of three Californian shrubs

Abstract: Background: Seedling recruitment following fire is an infrequent yet critical demographic transition for woody plants in Mediterranean ecosystems. Aims: Here we examine whether post-fire seedling recruitment of three widespread Californian chaparral shrubs is affected by local adaptation within an edaphically and topographically complex landscape. Methods: We reciprocally transplanted 6-month-old seedlings of Adenostema fasciculatum, Ceanothus cuneatus and Eriodictyon californicum to serpentine and sandstone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…In this context, we evaluated the effects of fragmentation and the barrier effect of a highway in a gypsum soil plant specialist, Lepidium subulatum, considering not only the landscape structure but also other indicators of ecological quality of the habitat remnants together with some population features. It have been emphasised that soil specialists could have reduced evolutionary potential because specialisation could constitute an evolutionary dead end if environmental conditions shift (Anacker et al, 2011;Bieger, Rajakaruna & Harrison, 2014). Nonetheless, recent evidences showed that population genetics of some gypsum specialists suggested a significant resilience and plasticity to adverse conditions -Nieto et al, 2012;García-Fernández et al, 2018;Matesanz et al, 2018;Cohen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we evaluated the effects of fragmentation and the barrier effect of a highway in a gypsum soil plant specialist, Lepidium subulatum, considering not only the landscape structure but also other indicators of ecological quality of the habitat remnants together with some population features. It have been emphasised that soil specialists could have reduced evolutionary potential because specialisation could constitute an evolutionary dead end if environmental conditions shift (Anacker et al, 2011;Bieger, Rajakaruna & Harrison, 2014). Nonetheless, recent evidences showed that population genetics of some gypsum specialists suggested a significant resilience and plasticity to adverse conditions -Nieto et al, 2012;García-Fernández et al, 2018;Matesanz et al, 2018;Cohen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Allocating more C to the root system helps maintain a positive water balance during dry periods and ensures the plants are well adapted to shallow soils. Of course, maternal effects can influence the results of local-adaptation studies; however, with the long-lived oaks, time constraints on experimental duration do not typically allow for direct fitness examination of offspring (Mousseau and Fox 1998;Wright and Stanton 2011;Bieger et al 2014).…”
Section: Seedling Growthmentioning
confidence: 99%
“…Habitat specialisation can have significant evolutionary consequences, often contributing to local adaptation (Leimu and Fischer 2008;Yost et al 2012;Bieger et al 2014) and speciation (Rajakaruna 2004;Kay et al 2011). Adaptive differentiation in response to distinct ecological pressures has long been recognised as a driver of species diversification (Darwin 1859;Clausen et al 1940;Ågren and Schemske 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on ultramafic plants, including Mimulus, Layia (Asteraceae), Collinsia (Plantaginaceae), Helianthus (Asteraceae), Noccaea and Lasthenia (Asteraceae), have contributed greatly to our understanding of factors and mechanisms underlying speciation (Kay et al 2011), demonstrating how edaphic specialisation can greatly reduce gene flow among divergent populations (via both pre-and postzygotic reproductive barriers), setting the stage for subsequent speciation. Ecological approaches, including reciprocal-transplant and common-garden experiments, have often been employed to examine local adaptation (Bieger et al 2014) and how ecological divergence can lead to reproductive isolation between closely related taxa (Wright and Stanton 2011;Yost et al 2012). Moyle et al (2012) showed that post-zygotic isolation via hybrid sterility can occur between adjacent ultramafic and non-ultramafic ecotypes, contributing to reduced gene flow and setting the stage for further genetic differentiation via edaphic specialisation.…”
Section: Physiology and Evolution (Session 4)mentioning
confidence: 99%